The Role of Marketing Innovation Mediation on The Influence of Organizational Creativity on Marketing Performance During The Covid-19 Pandemic Study on MSMEs Incorporated in Bojonegoro APMMIK - Andrik Wijayanto; Sanaji (Ilomata International Journal of Management, 2021)
This study aims to determine the effect of organizational creativity on marketing performance mediated by marketing innovations in MSMEs who are members of APMMIK Bojonegoro during the pandemic. The respondents used were 103 MSMEs owners, the test was carried out using the variant-based Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) alternative with the smartPLS 2.0 M3 program. Based on the results of the analysis, it can be concluded that organizational creativity has a positive and significant effect on marketing innovation, marketing innovation has a positive and significant effect on marketing performance, and organizational creativity has a negative and insignificant effect on marketing performance. The implementation of this research is to increase innovation during the pandemic so that MSME can continue to rise and develop.